WASTED? MANAGING DECLINE AND MARKETING DIFFERENCE IN THIRD TIER CITIES - Tara BRABAZON (Journal of Urban and Regional Analysis, 2022)
Third-tier cities are neglected in the research literature. Global and second-tier cities provide the positive, proactive applications of city imaging and creative industries strategies. However, small cities – particularly those who reached their height and notoriety through the industrial revolution – reveal few strategies for stability, let alone growth. This study investigates an unusual third-tier city: Oshawa in Ontario Canada. Known as the home of General Motors, its recent economic and social development has been tethered to the arrival of a new institution of higher education: the University of Ontario Institute of Technology. Yet this article confirms that simply opening a university is not enough to commence regeneration or renewal, particularly if an institution is imposed on unwilling residents. Therefore, an alternative strategy – involving geosocial networking – offers a way for local businesses and organizations to attract customers and provide a digital medication to analogue injustice and decay.